Subtemporal approach for posterior communicating artery aneurysms - Lan, Jing; Huang, Xiao; Liu, Yue; Zhang, Ting-bao; Chen, Jin-cao; Li, Zheng-wei (Frontiers in Neurology, 2024)
Background and objectivesDirect visualization of the aneurysmal neck and its related perforating arteries during microsurgical clipping of posterior communicating artery (PCoA) aneurysms with posterior projection or true PCoA aneurysms through the pterional approach may be difficult and complicated.MethodsFrom January 2022 to January 2023, the clinical and angiographic information regarding PCoA aneurysms were retrospectively collected. Among them, 10 consecutive patients with PCoA aneurysms treated with microsurgical clipping via the subtemporal approach in our single institution were included. Herein, we analyzed and summarized our experience and clinical outcomes to further evaluate the efficacy, safety and feasibility of this approach as well as the indications.ResultsAll aneurysms were completely clipped via the subtemporal approach. With respect to procedure-related complications, postoperative oculomotor nerve palsy occurred in one patient (10%), contralateral cerebral infarction in one patient (10%), and intraoperative rupture of the aneurysm in three patients (30%). There were no cases of temporal lobe contusion or venous injury in this group. Overall, Good outcomes were obtained in 9 patients (90%), and poor functional outcome was observed in 1 patient (10%) at the last follow-up.ConclusionThe management of true PCoA aneurysms and PCoA aneurysms projecting posteriorly is more complicated and challenging, and treating these lesions entails considerable risks via the pterional approach. Considering the above problems, we attempted to treat these refractory PCoA aneurysms through the subtemporal approach. Our results suggested that microsurgical clipping of these aneurysms via the subtemporal approach can achieve good clinical outcomes with a high preservation rate of the related branches. Appropriate patient selection, fully grasp of indications, precise understanding of the anatomy and thorough preoperative planning are crucial for successful surgery. The subtemporal approach appears to be a relatively safe and effective procedure in the experienced hands, and may be an alternative method for patients with true PCoA aneurysms or projecting posteriorly PCoA aneurysms which cannot be easily clipped from the pterional approach. It can provide a better lateral view to visualize the neck of the aneurysm, PCoA and its perforating vessels, as well as the other structures.